Active Ingredients: Exploring the Key Factors Affecting the Rising Cost of Developing New Drugs - Sarah J. Fossett; Phanindra V. Wunnava (Institute of Labor Economics (IZA), 2017)
What makes prescription drugs cost so much? The media and Congress say it is corporate greed, while pharmaceutical firms blame federal regulations and an expensive drug development process. This study focuses on R & D (R&D) expenditures at global pharmaceutical firms and explores the driving factors behind what makes R&D for prescription drugs so costly. By combining variables that represent the news media's claims (i.e. CEO compensation) and the pharmaceutical firms' rebuttals (i.e. late-stage drug development), this study attempts to add empirical evidence to the growing debate surrounding the high and rising cost of prescription drugs. The results suggest that there is some truth to both sides of the argument- specifically; both CEO compensation and phase II development are positively correlated with R & D expenditures. However, we have reason to believe that CEO compensation is more of an indicator of business strategy than greed. Finally, this study proposes possible research extensions for continued study.
Keywords: I11; J33; L10; 330; profitability; price earnings ratio; drug development; CEO compensation; prescription drugs; employee effect; Research & Development